Testing for the Existence of an S-curve in Croatia, Hungary, and Slovenia: A note - VASILEV, Aleksandar (Journal of Advanced Studies in Finance; Vol 10 No 1 (2019): JASF Volume X Issue 1(19) Summer 2019, 2019)
In this note we investigate for the existence of an S-curve for Croatia, Hungary and Slovenia. We interpret the results in the spirit of the international business cycle literature. In particular, we compare institutions across countries in the sample, their fiscal and monetary policies, whether they had currency and/or banking crises during the period of investigation, how much they trade with the rest of the world, and how similar or different those countries are compared to the evidence from international data.